An investigation into addressing expressions in english and in the jrai language. - Nguyễn,Thị Thanh (ĐHĐN., 2015)
This thesis presents address forms in English and in the Jrai language through their personal pronouns and kinship term systems. With the description their semantic features, and the range of using address forms, the learners can grasp the similarities and differences between the two languages in the terms of address terms. The knowledge about cultures of the two nations was also used to explain some similarities and differences in language usage of the two languages. Moreover, a variety of methods such as descriptive, analytical and synthetical methods, comparative and contrastive analysis were utilized as the main instruments to help the researcher in interpreting, describing and analyzing the data. The data upon which the study was based were also derived from interviews of Jrai villagers in Gialai Province as well as observation of both spontaneous and deliberative spoken discourse. The findings of the study showed the similarities and differences of the ways to use personal pronouns and kinship terms in English and in Jrai. Some other ways to address in both English and Jrai were also presented in this part. I also pointed out some suggestions to teach English address forms to the Jrai students effectively in this paper. The study also provided some implications for teaching and learning as well as suggestions for further research.